2013
DOI: 10.1007/s00787-013-0440-8
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary versus involuntary hospital admission in child and adolescent psychiatry: a German sample

Abstract: Involuntary psychiatric admission is a central issue in mental health care, especially in the treatment of children and adolescents. Its legal regulations do not only differ between European countries, but also on a federal level. Only few studies so far dealt with rates of involuntary admission (RIA), mainly focusing on adults, rather than children and adolescents. None of the studies analyzed this topic in a large cohort. The aim of this regional cross-sectional study was to compare voluntary and involuntary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 33 publications
5
43
0
2
Order By: Relevance
“…Research is increasingly focused on the use, effect, and patient’s perception or experience of coercive treatment forms, but little is published on adolescent patients. Coercion is present in adolescent mental health care: in Norway, 20% of admissions among 16- to 17-year-olds was involuntary [ 1 ], although it was 36.5% in a German sample [ 2 ]. Adolescent inpatients may also be subjected to forced medication or nutrition for treatment purposes, as well as other coercive measures, such as holding, mechanical restraints, seclusion, and medication, in order to prevent harm to people or property.…”
Section: Introductionmentioning
confidence: 99%
“…Research is increasingly focused on the use, effect, and patient’s perception or experience of coercive treatment forms, but little is published on adolescent patients. Coercion is present in adolescent mental health care: in Norway, 20% of admissions among 16- to 17-year-olds was involuntary [ 1 ], although it was 36.5% in a German sample [ 2 ]. Adolescent inpatients may also be subjected to forced medication or nutrition for treatment purposes, as well as other coercive measures, such as holding, mechanical restraints, seclusion, and medication, in order to prevent harm to people or property.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to adolescents, it has been reported that psychiatrists in Finland are of the opinion that the criteria for coercive care of minors should be broader than for adults and that coercive care should also be used as a preventive measure [ 21 ]. Two studies of medical records indicate that coercive care was associated with psychotic symptoms, mental retardation, temper tantrums, substance abuse, violent behaviour, and suicide risk [ 22 , 23 ]. In an earlier study from our research group [ 24 ], staff members in child and adolescent psychiatry were asked to describe work situations that contained some sort of ethical consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Then I would rely more on those who worked there. (6) Those who described good experiences with user participation referred to being included. As a result, the treatment was perceived as appropriate.…”
Section: To Gain Trustmentioning
confidence: 99%